Mediated Morality as a Middle Position in Understanding the Relation between God and Morality - Amund Tobias Måge Areklett; Atle Ottesen Søvik (Religions, 2023)
How should we understand the relation between God and morality? This article aims to address this question by constructing a theistic metaethical theory informed by postphenomenological mediation theory. According to postphenomenological mediation theory, properties and values are not independent entities but are instead mutually constituted through the relationships that they participate in. By emphasizing relationships and understanding goodness as harmony, the theory allows God and creation to jointly constitute goodness. This alternative theory is compared to the metaethical theories proposed by Robert M. Adams and Mark C. Murphy, which represent the two primary strands of theistic metaethics: theological voluntarism and natural law theory, respectively. The alternative theory exhibits certain advantages and resolves some of the issues found in Adams’ and Murphy’s theories.